(untitled) (Journal of Nematode Morphology and Systematics, 2012)
The identity of three South African species originally described as belonging to the genus Thonus is discussed. These species share a very similar morphological pattern mainly characterized by a unique combination of characters: cuticle dorylaimoid, lip region cap-like, pharyngeal expansion occupying about three-fi fths of total neck length, female genital system amphidelphic, pars refringens vaginae lacking or very reduced, tail rounded conoid and similar in both sexes, and 7-10 contiguous ventromedian supplements. Heynsnema gen. n. is erected to accommodate them. The new taxon resembles several qudsianematid and tylencholaimid genera, its relationships with them being analysed in detail; it is tentatively or provisionally classifi ed under the family Tylencholaimidae. New data of the three species are provided, including additional observations on their morphology, morphometrics and illustrations.